Effect of Different Concentrations of Silver Nanoparticles on the Quality of the Chemical Bond of Glass Ionomer Cement Dentine in Primary Teeth - Abed, Faisal Mohammed; Kotha, Sunil Babu; AlShukairi, Haneen; Almotawah, Fatmah Nasser; Alabdulaly, Rwan Abdulali; Mallineni, Sreekanth Kumar (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The nanotechnologies have been applied for dental restorative materials manufacturing such as glass ionomer cement, composites, tooth regeneration, and endodontic sealers. The study was aimed to investigate the chemical bond of conventional glass ionomer cement and to evaluate the addition of different concentrations of silver nanoparticles (AgNPs) on the quality of the chemical bond of glass ionomer cement to primary dentin. Methods: Silver nanoparticle (Ag-NPs) powder was added in concentrations of 0.2%, 0.4%, and 0.6% to the conventional powder of GIC Fuji II. Then, the powder was added to the liquid and mixed with the recommended powder/liquid ratio of 3.6:1g. The Fourier-transform infrared spectra (FTIR) of teeth with 0.2%, 0,4%, and 0.6% w/w of silver nanoparticles in GIC fills and the control tooth. The conventional glass ionomer was used as a control group. The control and the plain silver tooth were subjected to FTIR analysis using an ATR-FTIR spectrophotometer (ThermoFisher Scientific, Waltham, MA, USA) with ZnSe (Zinc selenide) ATR crystal (Attenuated total reflection) and OPUS v7.5 software. All spectra were recorded in the range of 500–3500 cm-1 in transmission mode with an ATR module. Results: The AgNPs added at 0.2%, 0.4%, and 0.6% concentration to GIC provided some information in the context of bond interaction with the dentin. Various bonds peaks were seen for calcium, carbonate, phosphate, and amide. In our study, only the amide and phosphate were generated. The amide peaks were almost similar to the control, 0.2%, 0.4%, and 0.6, with the peaks in the range of 1250–1650cm-1. There was a clear shift in the phosphate peak from the control, 0.2% and 0.4%, which were about 1050cm-1, whereas, for 0.6%, there was a clear shift from 1050cm-1 to 880cm-1. Conclusion: GIC supplemented with AgNPs showed that a concentration above 0.4% of AgNPs altered the bond quality in dentin interaction. In conclusion, adding AgNPs at a minimal level improves the mechanical properties and maintains the same bond quality as GIC.